Efektivitas Media Gambar Dalam Meningkatkan Hasil Belajar Ips Siswa Kelas Iii Sdn 12 Konda Konawe Selatan - Waode Ekadayanti (Jurnal Sultra Elementary School, 2022)
This study employs a Classroom Action Research (CAR) design, which consists of two cycles, each comprising four meetings. The procedure in each cycle includes planning, action, observation or evaluation, and reflection. The subjects of this study were 21 third-grade students of SDN 12 Konda, Konawe Selatan, consisting of 9 boys and 12 girls. The variables in this study are the use of picture media in social studies learning as the first variable, and learning outcomes, measured through students’ achievement scores after testing, as the second variable. The research results show that the use of picture media in Social Studies learning significantly improved students’ achievement. The average learning outcome score increased from 6.86 in the first cycle (categorized as “adequate”) to 8.06 in the second cycle (categorized as “high”). Furthermore, in the first cycle, only 12 out of 21 students (57.14%) met the Minimum Mastery Criteria (MMC), while in the second cycle, the number rose to 19 students (90.48%). The hypothesis test using the sign test also indicated that learning through picture media is effective in improving students’ Social Studies achievement in Class III of SDN 12 Konda, Konawe Selatan.